2022
DOI: 10.1097/prs.0000000000009181
|View full text |Cite
|
Sign up to set email alerts
|

A 12-Year Review of Clinical Practice Patterns in Dupuytren Contracture Based on Continuous Certification by the American Board of Plastic Surgery

Abstract: Background: The American Board of Plastic Surgery collects data on 20 common plastic surgery operations as part of the Continuous Certification process. The goal of this study was to describe clinical trends in Dupuytren contracture repair since 2008 as they relate to evidence-based medicine articles published in this timeframe. Methods: Cumulative tracer data for Dupuytren contracture were reviewed for the period from February of 2008 to March of 2020 and compared with evidence-based medicine articles publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 50 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…Thayer et al 14 demonstrated a similar increase in CCH utilization in their analysis of provider treatment patterns of Dupuytren’s disease in Medicare beneficiaries from 2012 to 2014. Moreover, in their review of practice patterns among plastic surgeons treating Dupuytren’s disease between 2008 and 2020, Yuksel et al 17 found an increase in the use of CCH when comparing practice patterns from 2008 to 2014 and 2015 to 2020 (0% versus 9%, P = 0.001). Altogether, these findings from the literature suggest that hand surgeons have readily adopted CCH into clinical practice since its introduction in 2010, but our findings along with those of Lipman et al suggest that since 2014, its utilization has remained relatively constant at almost a quarter of all procedures for Dupuytren’s disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thayer et al 14 demonstrated a similar increase in CCH utilization in their analysis of provider treatment patterns of Dupuytren’s disease in Medicare beneficiaries from 2012 to 2014. Moreover, in their review of practice patterns among plastic surgeons treating Dupuytren’s disease between 2008 and 2020, Yuksel et al 17 found an increase in the use of CCH when comparing practice patterns from 2008 to 2014 and 2015 to 2020 (0% versus 9%, P = 0.001). Altogether, these findings from the literature suggest that hand surgeons have readily adopted CCH into clinical practice since its introduction in 2010, but our findings along with those of Lipman et al suggest that since 2014, its utilization has remained relatively constant at almost a quarter of all procedures for Dupuytren’s disease.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have evaluated the treatment trends in patients with Dupuytren’s disease; however, most do not cover an adequate period after CCH was introduced to the market, and thus, it is generally inconclusive of how provider preferences have been influenced over the past 8 years 9,13,14 . The few recent studies that do investigate treatment trends in this setting may be limited by reporting and selection bias, as well as a lack of generalizability 9,15–17 . As such, there is a paucity in the existing literature of studies that aim to understand patient demographics of those receiving each treatment modality, the frequency and trends of such treatments, and their associated costs.…”
mentioning
confidence: 99%
See 1 more Smart Citation